Conflict Resolution in the Perspective of Contemporary Hadith - Asadori Azhari; Damanhuri (al-Afkar, Journal For Islamic Studies, 2024)
Islam is a religion of mercy for all humans and the universe. As stated in the Qur'an, the Prophet Muhammad SAW was sent as rahmatan lil 'alamin, including in order to create peace for all mankind on the face of the earth and avoid conflicts, even though conflicts still occur in parts of the world, so many of the Prophet's hadiths contain efforts to Efforts in handling conflict that are still relevant to be implemented are: 1). Conveying good things to the parties involved in the conflict, 2). Reconciling conflicting parties, 3). Conflict resolution with explanations from witnesses, 4). Be patient and pray for the party who triggered the conflict, 5). Shaking hands between the parties in conflict.